Analytical solutions for the study of homogeneous first-order chemical kinetics via UV–vis spectroelectrochemistry - Molina, A; Laborda, E; Gómez-Gil, J; Martínez-Ortiz, F; Compton, R (Elsevier, 2017)
Analytical solutions are reported for the identification and study of homogeneous chemical reactions via UV-vis spectroelectrochemistry. Expressions are presented for the concentration profiles and the absorbance response of any the species of the CEC mechanism when applying a potential-pulse perturbation under semi-infinite linear diffusion conditions. With this theory it is possible to relate easily the absorbance transient to the physicochemical dynamics of the redox system. In particular, the influence of the chemical reactions involving the oxidized and/or the reduced species will be investigated both in the normal and parallel beam configurations. Expressions for the reaction schemes CE, EC and E can be deduced as particular cases. The EC solutions are applied to the study of facilitated ion transfers across liquid. |. liquid interfaces where the likely different diffusivity of the ion in the two phases has been considered.